Peningkatan Prestasi Belajar Matematika Melalui Penerapan Metode Kooperatif Model TGT (Team Games Tournament) pada Siswa Kelas X TP 2 SMKN 4 Kota Serang - Rohaeni , N. Uyu Yuslimu (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
This research examined at the Team Games Tournament (TGT) model's cooperative approach as an option to enhance math learning ability in class X TP 2 SMKN 4 Kota Serang. This study employed a three-cycle classroom action research design, known as cycles I, II, and III. Tests and observations are utilized as data collecting strategies. The study's findings show that using the TGT model's cooperative approach greatly raises pupils' mathematical proficiency. The cooperative approach of the TGT model may be utilized as an alternative to studying mathematics to increase student accomplishment, according to the data analysis results. The study's findings demonstrate that the model has a beneficial effect as seen by the improvement in student learning completion and average student score. The data analysis also reveals that there is a decent amount of activity among students' and instructors' learning-related activities.